Relationship commitment regulation: Influencing a partner's commitment to achieve one's commitment goals - MACHIA, Laura V. (Institutional Knowledge at Singapore Management University, 2024)
We introduce a model of relationship commitment regulation, which describes how romantic partners might use empirically-validated antecedents of commitment level strategically to influence a partner's commitment toward their relationship based on certain commitment goals they have for the relationship. People are generally aware of and relatively accurate with respect to knowing their partner's level of commitment and also have preferences regarding their desired level. We summarize key antecedents of commitment level (i.e., satisfaction level, alternative quality, investment size, future plans, and subjective norms) and then describe how each can be manipulated via relationship maintenance activities to move a partner's commitment level up or down, or maintained at a desired current level. Collectively, the model provides a strategic roadmap for actions one can take to foster desired commitment in one's partner and provides insight into the dyadic processes and outcomes of relationship maintenance.